Examining the Indirect Effects of Perceived Organizational Support for Teamwork Training on Acute Health Care Team Productivity and Innovation: The Role of Shared Objectives. Issue 3 (June 2018) - Lyubovnikova, Joanne; West, Thomas H. R.; Dawson, Jeremy F.; West, Michael A.
This study examines the relationship between a specific type of team climate for perceived organizational support, team perceived organizational support for teamwork training (team POS-TT), and its effects on the productivity and innovation of acute health care teams. Drawing on organizational support theory, we examine how this relationship emerges via the mediating mechanism of shared objectives. Using survey data from 88 teams based in 13 health care organizations across the United Kingdom, we found support for the indirect effects of team POS-TT via shared objectives, but not for the direct effect of team POS-TT, thus indicating a mediated relationship with team productivity and innovation. As predicted, through the satisfaction of important esteem and affiliation needs of team members, team POS-TT compelled teams to engage in the process of generating shared objectives, which, in turn, positively predicted team productivity and innovation. These findings contribute to the scant literature on perceived organizational support (POS) as a form of team climate, and respond to recent calls to consider different types of POS by focusing on perceived support for teamwork training, an area which has particular relevance in the context of health care. Furthermore, the study serves to extend understanding regarding exactly how team POS-TT affects team outcomes via the specific process of shared objectives. We conclude with a discussion of these contributions to the literature and delineate several practical implications for leaders and managers in health care organizations.